Improved mental health for women receiving infant mental health home visiting: a randomized controlled trial - Jester, Jennifer M.; Stacks, Ann M.; Riggs, Jessica L.; Brophy-Herb, Holly E.; Muzik, Maria; Rosenblum, Katherine; , Michigan Collaborative for Infant Mental Health Research; Alfafara, Emily; Barron, Carla; Brophy-Herb, Holly E.; Erickson, Nora L.; Fitzgerald, Hiram E.; et al. (Frontiers in Psychology, 2025)
IntroductionThis study evaluates the impact of a home-based infant mental health intervention on maternal mental health symptoms. Prevalence rates of maternal depression, anxiety and trauma symptoms are quite high during the postpartum period and can contribute to ruptures in the parent–child relationship and infant development. While some infant mental health interventions improve depression, less is known about the impact of home-based or attachment-based psychotherapeutic interventions on maternal anxiety or post traumatic stress disorder.MethodUsing a randomized controlled trial design, mothers with infants were recruited and randomized to infant mental health home visiting (IMH-HV; n = 38) or a control group (n = 35). However, five dyads who were assigned to the treatment group but received no treatment were omitted from the analysis, for a per-protocol analysis of 68 mothers. Mothers reported on their depression (Patient Health Questionnaire, PHQ-9), anxiety (General Anxiety Disorder, GAD-7), and trauma symptoms (PTSD Checklist, PCL-5) at baseline, and six and 12 months later.ResultsThe mothers in the per-protocol treatment group (n = 33) demonstrated greater decreases in mental health symptoms over the 12 months of the study than those in the control group (n = 35) (slope effects: for depression (−0.19, p = 0.015), anxiety (−0.13, p = 0.058), and trauma (−0.46, p = 0.057)).DiscussionResults suggest that IMH-HV services are effective in reducing mental health symptoms for mothers who actually received treatment.Clinical trial registrationNCT03175796